2023
DOI: 10.7759/cureus.42311
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Current Literature on Pleomorphic Adenoma

Abstract: Pleomorphic adenomas (PA) are the most common benign salivary gland tumors. They arise from the major salivary glands, as well as the minor salivary glands. They may arise rarely from the palate, oral cavity, neck, and nasal cavity also. Yet, the fourth, fifth, and sixth decades of life are the most common for them to manifest. Forty percent of them occur in males and 60% in females. It is a benign mixed tumor, which has three components: an epithelial component, a myoepithelial cell component, and a mesenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…To confirm the final diagnosis, immunohistochemical markers such as p63, WT1, Mcl-2, Glial fibrillary acidic protein (GFAP), smooth muscle actin (SMA), S100, metastasis suppressor gene (NM23) and SRY-box transcription factor 10 (SOX10)were used. 16 According to Sharma et al, 39 patients observed that one patient had Frey syndrome and another few disrupted permanent facial nerves. 17 The treatment of pleomorphic adenoma is surgically excised.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the final diagnosis, immunohistochemical markers such as p63, WT1, Mcl-2, Glial fibrillary acidic protein (GFAP), smooth muscle actin (SMA), S100, metastasis suppressor gene (NM23) and SRY-box transcription factor 10 (SOX10)were used. 16 According to Sharma et al, 39 patients observed that one patient had Frey syndrome and another few disrupted permanent facial nerves. 17 The treatment of pleomorphic adenoma is surgically excised.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation exposure has been postulated as a well-known environmental risk factor. Also, there are some evidences suggesting that the oncogenic simian virus (SV40) could potentially contribute to onset or progression of pleomorphic adenoma [ 5 ]. This tumour has a female preponderance affecting middle-aged women between 30 and 50 years [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It usually presents as hard, uneven nodular swelling in the parotid region and usually asymptomatic with slow growing tendency without facial nerve involvement. However, if left untreated, they can grow into extensive sizes [ 5 , 7 , 8 ]. Approximately 6 % of PA tends to malignant transformation into Carcinoma Ex-pleomorphic adenoma, an aggressive tumour.…”
Section: Introductionmentioning
confidence: 99%